2020
DOI: 10.33314/jnhrc.v18i2.2484
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Prevalence and Correlates of Substance Abuse Amongst the Adolescents of Dharan, Eastern Nepal

Abstract: Background: The burden of substance abuse amongst the youths has increased worldwide including Nepal. There is limited data on prevalence of substance abuse among the adolescents. Hence this study aims to determine the prevalence of substance abuse amongst the adolescents of Dharan, Eastern Nepal.Methods: A cross-sectional study was conducted from July 2018 to December 2018. Self-administered structured questionnaire adapted from National Youth Survey sponsored by the Centre for Substance Abuse Prevention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Other studies have reported a lower prevalence of tobacco use (12% to 46%) in youths. 8,12 In our study 37.8% used alcohol. Our finding is similar to that of another study from Eastern Nepal, reporting a prevalence of 37% of youth as alcohol users.⁸ Similarly, 39.4% of students of Goa, India also reported alcohol use.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Other studies have reported a lower prevalence of tobacco use (12% to 46%) in youths. 8,12 In our study 37.8% used alcohol. Our finding is similar to that of another study from Eastern Nepal, reporting a prevalence of 37% of youth as alcohol users.⁸ Similarly, 39.4% of students of Goa, India also reported alcohol use.…”
Section: Discussionmentioning
confidence: 55%
“…A similar finding was also reported in Eastern Nepal. 8 Another study reported that 67.5% of youths had a family history of alcohol use which was especially seen in their fathers. 13 In our study, the majority (29.7%) reported curiosity as the main reason followed by imitation (25.4%) and peer pressure (21.4%) for using substances.…”
Section: Substance Use Prevalence Among Youthsmentioning
confidence: 99%
See 1 more Smart Citation
“…A national survey on drug use conducted in Nepal in 2020 reported tobacco (mostly in form of cigarettes) as the most commonly (96.8%) used substance, followed by cannabis (84.7%), tranquilizers (73.1%), alcohol (64.8%), opiates (46.6%), inhalants (3.9%), stimulants (2.4%), hallucinogens (1.1%), and other types of drugs (31%) [36]. Substance use is also highly prevalent among school adolescents in Nepal [37].…”
Section: Nepalmentioning
confidence: 99%